Efficacy of mobilisation with movement in chronic shoulder pain: protocol for a systematic review and meta-analysis of controlled trials - Martin Bjørn Stausholm; Jon Joensen; Jan Magnus Bjordal; Arnstein Storås; Fabian Lillebostad; Sturla Haslerud (BMJ Open)
Introduction Shoulder pain affects approximately one in four adults and is thus one of the most common musculoskeletal problems. Only 50% of patients who begin treatment for shoulder pain are cured within 6 months. There is a need for systematic reviews to estimate the effectiveness of shoulder treatments. We decided to evaluate the effect of mobilisation with movement (MWM) on chronic shoulder pain in a systematic review.Methods and analysis The review will include controlled trial articles identified via five electronic databases (PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature, Physiotherapy Evidence Database and Cochrane Central Register of Controlled Trials), reference lists, citations searches and experts in the field. Only controlled trials involving participants with a mean duration of pain of ≥3 months, in which the effectiveness of MWM has been compared with non-invasive treatments, sham mobilisation or wait-and-see will be included. The included trials will be synthesised with random effects meta-analyses. Risk-of-bias will be assessed with the Physiotherapy Evidence Database 0–10 point scale.Ethics and dissemination The review does not require ethics approval as it is based on anonymised data from trial reports. The results of the review will be disseminated through a peer-reviewed publication.PROSPERO registration number CRD42018109380.